The Effectiveness of Blended Learning by Using Wiki in Developing on Writing Skills among male and female Basic Grade Six Students in The Sultanate of Oman - Alshabibi, Amal Saleem Mohammed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to test the effectiveness of blended learning using wiki in developing written expression skills for sixth grade students. The researcher used the quasi-experimental approach. To achieve this, the researcher adopted an achievement test and a list of skills for written expression. that was previously presented to a group of specialized referees to ensure their validity. And the test reliability is calculated by internal consistency. The study sample was divided into two experimental groups that included 30 students who studied the description lesson in the book My Writing Skills through the application of wiki, and a control sample of 30 students studied the same lesson in the traditional way, and after completing the experiment, a written expression skills test was applied to the two groups. The results indicated that there were statistically significant differences at the level of significance (0.05≥α) between the mean scores of the two experimental groups and obtained an overall average (34.57 out of 42), in contrast to the control receiving an overall average (30.33 out of 42), in a test attributed to the blended learning strategy. By using wiki, and in basic skills of written expression, where the experimental in the content skill got an average (14.7 out of 18) and the control got (12.8) and in the skill of form and organization; Empiric got average (7.77 out of 9) control (7.33), and finally language and style skill; The experimental got a mean (12.1 out of 15), while the control (10.2). The differences were statistically significant in the skills of content, language and style in favor of the experimental group, while the differences between the two groups were not significant in the skill of form and organization, Based on these results, the researcher recommended paying attention to developing written expression skills among students by adopting blended learning using wiki and training Arabic language teachers on how to use it, in addition to expanding the use of blended learning strategy using wiki to teach other Arabic language skills such as reading and grammar.